2014
DOI: 10.2478/mgrsd-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization: Concepts, Trends and Analysis in Three Latin American Cities

Abstract: Explanatory models on the urban expansion process have focussed mainly on the dynamic of cities in the developed countries that are characterized by a strong institutional framework, a culture of urban planning, and compliance with the rules. This paper analyses the phenomenon of urban expansion in three Latin American cities (Buenos Aires, Santiago de Chile and Mexico City), taking into account cities with a strong process of urbanization and where the local administration does not have enough control over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…These two groups tend to have infrastructures, equipment, and services that are similar to those offered by large cities while maintaining certain advantages in matters of governance and quality of life. However, they still lag behind in several dimensions, such as access to education, culture, recreation, high levels of technological diversification, and other benefits (Piña 2014;Rodríguez 2017). Finally, the 20,000-inhabitant threshold is conventionally used in comparative studies as a guarantor of proper urban conditions in Latin America.…”
Section: Settingsmentioning
confidence: 99%
“…These two groups tend to have infrastructures, equipment, and services that are similar to those offered by large cities while maintaining certain advantages in matters of governance and quality of life. However, they still lag behind in several dimensions, such as access to education, culture, recreation, high levels of technological diversification, and other benefits (Piña 2014;Rodríguez 2017). Finally, the 20,000-inhabitant threshold is conventionally used in comparative studies as a guarantor of proper urban conditions in Latin America.…”
Section: Settingsmentioning
confidence: 99%
“…Urban compounds are difficult because of the arrangement of recent urban networks containing major cities contributing to the approach to the integration of recent urban midpoints, which rapidly attain one million inhabitants and an adequate concentration of fundamental urban supplies. The development of intermediate cities produces other processes, for instance suburbanization, peri-urbanization and counter urbanization, which is associated in Latin America with the urbanization process as well as unrevealed urbanization [76]. Megeri, Kadi and Kengnal [77] reported that the trend of urbanization in India occurs on a larger magnitude because of the demographic abilities.…”
Section: Urbanization In the Northern Corridor Economic Regionmentioning
confidence: 99%
“…Urbanization and socioeconomic elements show that in the three cities, notably Buenos Aires, Santiago de Chile and Mexico City, enhancements in the standard of living produce a decline in slums and poverty, displaying that socioeconomic elements have a direct connection with urbanization that essentially grow cyclically; in times of downturn the cities broaden horizontally if land is low-priced, and integrate in times of economic development. Latin America is forming more areas with rising needs for public supplies, infrastructure and the labour market [76].…”
Section: Author Detailsmentioning
confidence: 99%
“…The researches (development plans and models) are focused mainly on cities with an organized institutional framework and a culture of urban planning. These studies are very scarce in the case of cities with a high rate of urbanization and local administration, insufficient control over the growth of the city, strong internal and international migration processes (Piña, 2014) and a high level of informality (more than 60 per cent).…”
Section: Introductionmentioning
confidence: 99%
“…The development process of Latin American cities has been characterized by disorganized and scattered growth in vulnerable ecological zones, environmental deterioration, reduction of the area for food production and social and territorial inequalities increase (Piña, 2014). For this reason, in Latin American cities, it is a priority to know the current state and create policies for the city's sustainable development (Merchan, 2015;Cuevas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%